EXTRACTION OF NATURAL COMPOUNDS FROM CALLUS INDUCTED OF COMMON SAGE PLANT Salvia officinalis L. AND THEIR EVALUTION OF ANTIOXIDANT ACTIVITY - S. I. Neamah; A. F. Almehemdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Common sage (Salvia officinalis L.) is a medicinal plant well known for its pharmacological properties. The current study was tested by the MTT assays to determine the inhibitory of free radical scavenging capacity of natural compounds In vivo, and stimulation of production because its important products in pharmaceutical industry by using different concentrations of methyl jasmonate in callus of inducted from hypocotyl and cotyledon, with different the solvent of extract. The extraction was carried out at the department of Medical Research- Ministry of Sciences and Technology. The results showed that the explant, concentration of methyl jasmonate and interaction between studied facters significantly effected at the MTT assay. The callus of inducted from cotyledon gave the highest activity with absorbance reached 0.375, 0.422, and 0.562, when used the solvent of extract hexan, ethyl acetate, and methanol, respectively. The concentrations of methyl jasmonate caused by a significant reduction in the MTT assay, When using ethyl acetate as a solvent for extracting callus gave an absorbance value of 0.420 at 300 µM concentration of methyl jasmonate. While, the concentration 200 µM of methyl jasmonate gave the highest of absorbance 0.576 when using methanol the solvent of extract. The interaction of the two studied factors of the experiment significantly effected all the solvents of extraction.